Peningkatan dimensi bernalar kritis mata pelajaran pendidikan pancasila materi pancasila dalam kehidupanku melalui model group investigation pada peserta didik kelas 5 sekolah dasar - Sa'diyah, Maulina; Adi, Fadhil Purnama (Didaktika Dwija Indria, 2026)
One of the 6 dimensions in the Pancasila learner profile that students must have is critical reasoning. The purpose of this study to improve the ability to reason critically in learning Pancasila Education through the application of the group investigation model in grade V elementary school students. The method in this research is a classroom action research method (PTK) carried out in two cycles. The research subjects were students of class VB SDN Nayu with a total of 27 students. The data collection techniques used were observation, interviews, documentation, and tests. Triangulation of techniques and sources is a method of testing validity. Initial conditions showed the percentage of 22%, cycle I meeting 1 increased to 30%, and at meeting 2 the percentage of completeness was 52%, the average in cycle I was 37%. In cycle II meeting 1 the percentage of completeness was 74% and at meeting 2 it increased to 93%, the average in cycle II was 89%. Based on the results of the study, it can be concluded that the application of the group investigation learning model can improve the ability to reason critically in learning Pancasila Education in class VB students of SDN Nayu.